Education on live pharmacy plants and the use of small land in Sungai Musang Village - Awilda, Pertiwi; Chairul; Nurwahida; Nurrahmah, Sheila; Rizwarini, Siti Rahma; Bawaihi (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
Knowledge about the use of yard land for live pharmacy plants or family medicinal plants (toga) is not yet well understood by the people of Sungai Musang village, which is shown by the yard land around people's houses which has not been planted with live pharmacy plants. The aim of this service is to provide education to the public regarding live pharmacy plants and to be able to utilize the narrow land around the house to plant live pharmacy plants. The method given is a lecture about the meaning of a living pharmacy, types of plants, the benefits of a living pharmacy, and how to process medicinal plants. Followed by questions and answers and distributing leaflets to participants. Another activity is to provide an example of making a living pharmacy for a narrow area from wooden shelves and mini pots. Participants were very enthusiastic about taking part in this activity, most of the participants gained knowledge about living pharmacies and their uses and were expected to be motivated to make their own in their own yards.